2015
DOI: 10.1128/jb.00039-15
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of the Interaction between the TpsA and TpsB Proteins in the Haemophilus influenzae HMW1 Two-Partner Secretion System

Abstract: The two-partner secretion (TPS) pathway in Gram-negative bacteria consists of a TpsA exoprotein and a cognate TpsB outer membrane pore-forming translocator protein. Previous work has demonstrated that the TpsA protein contains an N-terminal TPS domain that plays an important role in targeting the TpsB protein and is required for secretion. The nontypeable Haemophilus influenzae HMW1 and HMW2 adhesins are homologous proteins that are prototype TpsA proteins and are secreted by the HMW1B and HMW2B TpsB proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The POTRA domains might thus contribute to addressing the TpsA protein to the pore of the TpsB transporter. Similar suggestions were made for the POTRA domains of HMW1B and LepB (Garnett et al, 2015 ; Grass et al, 2015 ). Their role in shuttling the passenger to the barrel might explain why PlpD, the prototypic Vd protein, harbors a POTRA-like domain.…”
Section: Pathway Of Tpsa Proteins Across the Cell Envelopesupporting
confidence: 69%
See 4 more Smart Citations
“…The POTRA domains might thus contribute to addressing the TpsA protein to the pore of the TpsB transporter. Similar suggestions were made for the POTRA domains of HMW1B and LepB (Garnett et al, 2015 ; Grass et al, 2015 ). Their role in shuttling the passenger to the barrel might explain why PlpD, the prototypic Vd protein, harbors a POTRA-like domain.…”
Section: Pathway Of Tpsa Proteins Across the Cell Envelopesupporting
confidence: 69%
“…The TPS domain of the TpsA protein must be in an extended conformation for interaction with the POTRA domains of the TpsB transporter, as shown for the FHA/FhaC and HMW1/HMW1B pairs (Hodak et al, 2006; Grass et al, 2015). Surface plasmon resonance experiments with the FHA/FhaC pair have indicated interactions of micromolar affinity between the two proteins and suggested that association and dissociation occur very fast (Delattre et al, 2011).…”
Section: Pathway Of Tpsa Proteins Across the Cell Envelopementioning
confidence: 96%
See 3 more Smart Citations